Enrichment of health insurance claims data with official death certificate information from three German cancer registries: Proportions of successful linkages and differences by region, year, and age - Heinze, Franziska; Langner, Ingo; Bartholomäus, Sebastian; Meyer, Martin; Kieschke, Joachim; Maaser, Kerstin; Czwikla, Jonas (Das Gesundheitswesen, 2025)
Evaluating breast cancer mortality in the German mammography screening program with health insurance claims data requires the availability of claims data with information on causes of death. This work aimed to determine the proportions of successful cause-of-death linkages between the second-largest German statutory health insurance fund and three federal cancer registries and to investigate whether linked proportions differed by region, year, and age. Women aged 40–90 years whose insurance was terminated between 2006 and 2018 were included. Proportions successfully linked to the official death certificate databases of all individuals (available in one registry) and of registered cancer cases (available in three registries) were calculated. Of 150,369 women whose insurance was terminated due to death, 90.0% were linked to the database including all deceased women. Regarding the databases including only registered cancer cases, 35.9% of 150,369, 38.6% of 47,472, and 20.1% of 65,893 deceased women were linked. Linked proportions increased from 2006 to 2018 and peaked in age group 60–69 years. The data will be used for the evaluation of the German Mammography screening program. Since causes of death were not linked for all deceased women and the proportions of linkages differed by region, year, and age, claims-based algorithms will also be considered to complement claims data with causes of death.
Keywords: claims data; record linkage; cause of death; cancer registry; routine data